Chemical dynamics in extreme environments - Rainer A. Dressler (World Scientific, 2001)
As computing power increases, a growing number of macroscopic phenomena are modeled at the molecular level. Consequently, new requirements are generated for the understanding of molecular dynamics in exotic conditions.This book illustrates the importance of detailed chemical dynamics and the role it plays in the phenomenology of a number of extreme environments. Each chapter addresses one or more extreme environments, outlines the associated chemical mechanisms of relevance, and then covers the leading edge science that elucidates the chemical coupling. The chapters exhibit a balance between theory and experiment, gas phase, solid state, and surface dynamics, and geophysical and technical environments.